The Circus Star - Invader Limited (Invader Limited, 1992)
Corky,the Pig,is the groom in Mr Whistle's circus,but he dreams of being a star in the show.It does not seem likely until,one day,Corky gets his chance...
Keywords: Juvenile literature-Fiction